Rapidly Invasive Buschke-Löwenstein Tumor Associated With Human Papillomavirus Types 6 and 52. Issue 10 (October 2015) - Diani, Marco; Boneschi, Vinicio; Ramoni, Stefano; Gadda, Franco; Del Gobbo, Alessandro; Cusini, Marco
<x xml:space="preserve">Abstract</x> Abstract Buschke-Löwenstein tumor, or giant condyloma acuminatum, represents a rare, sexually transmitted disorder, with a slow evolution and the tendency to infiltrate in the adjacent tissues associated with human papillomavirus (HPV). This article reports the first case of male Buschke-Löwenstein tumor associated with HPV6 and HPV52.